Drowning as a Method of Suicide Case Report - Özdemir, Çağlar; Tuğcu, Harun; Asil, Haşim; Yorulmaz, Coşkun (The Bulletin of Legal Medicine, 2007)
Determination of cause and manner of death in drowning cases may be possible in the light of crime scene investigation, necropsy, psychological autopsy findings and the laboratory analysis together. A 69 years old man, was found water and reported as suicidal drowning, is presented with crime scene investigation and all postmortem examination findings integrating each other.Key words: Drowning, suicide, autopsy, crime scene investigation
Keywords: drowning; suicide; autopsy; crime scene investigation